Advance of performance modeling for Turbo receivers - Yun XUE; Bin JIANG; Xi-qi GAO (Tongxin xuebao)
Aiming at the performance modeling for Turbo receivers,the research results are summarized,in the mean-while,the characteristics and future trends are concluded in terms of equivalent model,transitive parameter,performance abstraction and transitive relation.The Gaussian distribution of equivalent model for log-likelihood ratiois the founda-tionof performance modeling research.Representative methods for application scenarios such as performance analysis,performance optimization and joint design with link are to derive the transfer chart with mutual information as transitive parameter,to derive semi-analytical transitive relation with bit error rate or fidelity as transitive parameterand to derive semi-analytical transitive relation with mutual information as transitive parameter,respectively.These methods represent the development direction of performance modeling for turbo receivers.